The Experience of Hypoglycaemia and Strategies Used for Its Management by Community-Dwelling Adults with Diabetes Mellitus: A Systematic Review - Tan, S.; Chen, H.; Taylor, B.; Hegney, Desley (University of Adelaide, 2011)
Background: Hypoglycaemia, a common complication of diabetes drug therapy, has been reported to influence therapy adherence and the quality of life of people with diabetes mellitus. No systematic reviews on the experience of hypoglycaemia have been undertaken. The extant literature has taken a medical model perspective focusing on the causes, prevalence, and impact of hypoglycaemia. To understand the meaningfulness of hypoglycaemia and how this condition impacts on a person with diabetes mellitus, a systematic review was undertaken exploring the experiences of hypoglycaemia in community-dwelling people with diabetes mellitus. Objective: This review aimed to synthesise evidence on the experience of hypoglycaemia, and the strategies used to control it in community-dwelling adults with type 1 and type 2 diabetes mellitus. Inclusion Criteria: Type of Participants – Community-dwelling adults (18 years of age and over) who had experienced hypoglycaemia from type 1 or type 2 diabetes mellitus and/or who had used self-management strategies for hypoglycaemia were included. Phenomena of Interest – The experiences of hypoglycaemia in community-dwelling adults with diabetes mellitus and the strategies they used to self-manage hypoglycaemia were included. Type of Studies – Qualitative studies including, but not limited to, designs such as phenomenology, grounded theory, ethnography, action research and feminist research were included.Search Strategy: Published and unpublished studies in English from January 2000 to August 2010 were gathered using a three-step search strategy. An initial limited search was conducted in MEDLINE and CINAHL to identify keywords and index terms, which were then used in a second search across the CINAHL, PUBMED, SCOPUS, PsycINFO, PsycARTICLES, Web of Science, JSTOR, EMBASE and MEDNAR databases. Additionally, the reference list of all studies was hand-searched for additional studies. Methodological Quality: Two reviewers independently assessed the retrieved studies for methodological validity, using standardised Joanna Briggs Institute-Qualitative Assessment and Review Instrument (JBI-QARI) critical appraisal instruments. Disagreements that arose between the two reviewers were resolved with the help of a third reviewer. Data Collection: Data, in terms of research findings, were extracted from included studies using the standardised JBI-QARI data extraction tool. Data Synthesis: These findings were then pooled and assembled into level 1 findings, then level 2 findings (categories), and lastly meta-synthesised to form one level 3 synthesised finding. Meta-aggregation was carried out using JBI-QARI. Results: Six studies were included in the review. Participants who lived independently in the community and attended primary care or outpatient clinics were included. In total, twenty findings were grouped into three categories, which were synthesised into one overall finding–i.e., “People with diabetes mellitus can self-manage their diabetes and thus prevent hypoglycaemic episodes more effectively when health professionals provide psychological, physiological and spiritual support, and an individually targeted education programme”.Conclusions: The review findings revealed patient-identified priorities to maintain normality in blood glucose self-management. There is also evidence that some people lack the knowledge to identify and self-manage hypoglycaemia. Implications for Practice: To enable community-dwelling adults with diabetes mellitus to self-manage hypoglycaemia, healthcare professionals should provide individualised information and emotional support, and regularly discuss and assess the person’s level of knowledge, awareness of hypoglycaemia, and their ability to self-manage. Implications for Research: There is a lack of data that capture the person’s experience and awareness of hypoglycaemia and how they self-manage the condition, particularly in varying cultural contexts. A mixed-method study could be designed to explore the experiences of hypoglycaemia, and to develop and validate a reliable tool that assesses the level of knowledge and awareness of hypoglycaemia, and the ability to self-manage. This study should include people with diabetes mellitus from different cultures and/or geographical locations.